Extracellular ATP Regulates CD73 and ABCC6 Expression in HepG2 Cells - Martinelli, Fabio; Cuviello, Flavia; Pace, Maria C.; Armentano, Maria F.; Miglionico, Rocchina; Ostuni, Angela; Bisaccia, Faustino (Frontiers in Molecular Biosciences, 2018)
The ATP-binding cassette sub-family C member 6 transporter (ABCC6) is an ATP dependent transporter mainly found in the basolateral plasma membrane of hepatic and kidney cells. Mutations in ABCC6 gene were associated to the Pseudoxanthoma elasticum (PXE), an autosomal recessive disease characterized by a progressive ectopic calcification of elastic fibers in dermal, ocular and vascular tissues. It is reported that the over-expression of ABCC6 in HEK293 cells results in the cellular efflux of ATP and other nucleoside triphosphates, which in turn are rapidly converted into nucleoside monophosphates and pyrophosphate (PPi). Since PPi is an inhibitor of mineralization, it was proposed that the absence of circulating PPi in PXE patients results in the ectopic mineralization, a typical feature of PXE. In addition to pyrophosphate, in the extracellular space, ATP is converted by an ectonucleosidase in AMP which in turn is transformed into adenosine and phosphate. ABCC6 protein is thus involved in the production of adenosine and therefore on the activation of the purinergic system. In the liver, purinergic signaling has been shown to regulate key basic cellular functions. Our previous studies showed that in ABCC6 knockdown HepG2 cells the expression of some genes, related with the calcification processes, is dysregulated. In this work, experiments have been carried out in order to verify if ABCC6, besides supplying the pyrophosphate necessary to prevent the mineralization of soft tissues, also plays a role in the activation of the purinergic system. For this purpose, the transport activity of ABCC6 was blocked with Probenecid and the expression of ABCC6 and NT5E was analyzed with real time PCR and western blotting. The results of this study showed that both proteins are downregulated in the presence of Probenecid and upregulated in the presence of adenosine or ATP.